BRAF inhibition in refractory hairy-cell leukemia - Dietrich, Sascha; Glimm, Hanno; Andrulis, Mindaugas; Kalle, Christof von; Ho, Anthony Dick; Zenz, Thorsten (The New England journal of medicine, 2012)
To the Editor: Hairy-cell leukemia (HCL) is a mature B-cell lymphoid cancer that is commonly treated with purine analogues.1 Virtually all patients with HCL carry the BRAF V600E mutation, which constitutively activates the MEK-ERK pathway and which can be inhibited in vitro by the mutation-specific BRAF inhibitor PLX-4720.2 BRAF mutations have been identified in melanoma but are found across cancers.3 An inhibitor of mutated BRAF (vemurafenib) has transformed the treatment of melanoma. It is unclear whether this clinical efficacy can be extrapolated to other cancers.4,5 We used vemurafenib in a patient with refractory HCL and a pressing need for . . .
Gesehen am 29.03.2018